PENERAPAN QUICK RESPONSE CODE DALAM AKSES JARINGAN INTERNET MENGGUNAKAN MIKROTIK ROUTERBRAND RB941-2ND HAP - Nanang Qosim (JISTech (Journal of Islamic Science and Technology), 2019)
Application of Quick Response Code (QR Code) in accessing the internet network using RouterBrand Mikrotik. Settings in the RouterBrand Mikrotik that can emit a host can be used in accessing the internet network. Using Mikrotik RouterBrand in bandwidth management integrated with Hospot regularly can share bandiwitch flexibly to internet network users so as to provide convenient internet access with a stable bandwidth. Applying the Quick Response Code for internet network access so that it's easier, practical and efficient. However, the use of the Quick Response Code must have a QR Code scanner, without the QR Code scanner not being implemented.